2013
DOI: 10.4161/adip.24722
|View full text |Cite
|
Sign up to set email alerts
|

Loss of menin mediated by endothelial cells treated with CoPP is associated with increased maturation of adipocytes

Abstract: Oxidative stress is caused by an increase in reactive oxygen species (ROS) relative to the antioxidant defense system. An increase in ROS is known to decrease vascular function, increase inflammatory cytokines, and promote adipocyte hypertrophy. A known regulator of the oxidative stress response is the heat shock protein, heme-oxygenase 1 (HO-1), which is induced by cobalt protoporphyrin IX (CoPP). Menin was recently found to promote the sustained expression of heat shock proteins and is implicated in the regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…( 13 , 15 ) ROS, in turn, are thought to induce adipocyte hypertrophy, which contributes to the progression of obesity. ( 17 ) Numerous reports have suggested that oxidative stress and obesity are exacerbated when those two factors interact with each other. ( 18 , 19 ) Although further studies are required to elucidate the mechanism underlying the induction of oxidative stress in TSOD mice, our findings suggest that oxidative stress in young TSOD mice is attributed to ROS production associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…( 13 , 15 ) ROS, in turn, are thought to induce adipocyte hypertrophy, which contributes to the progression of obesity. ( 17 ) Numerous reports have suggested that oxidative stress and obesity are exacerbated when those two factors interact with each other. ( 18 , 19 ) Although further studies are required to elucidate the mechanism underlying the induction of oxidative stress in TSOD mice, our findings suggest that oxidative stress in young TSOD mice is attributed to ROS production associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, patients affected by the MEN1 syndrome have been reported to show benign white fat tumours (lipomas) with loss of the wild‐type MEN1 allele , and it has been suggested that lipomas are overrepresented in this syndrome as compared with the general population . Furthermore, it has been shown that downregulation of the protein product of MEN1 – menin – is associated with the induction of PPARG and an increase in the number of mature adipocytes . Peroxisome proliferator‐activated receptor‐γ (PPARG) is a major regulator of adipogenesis; it is both necessary and sufficient for this process, as it is able to transdifferentiate fibroblasts and myoblasts into adipocytes .…”
Section: Resultsmentioning
confidence: 99%